Occupational Stress and Coping Mechanisms of Inbound Call Center Agents of a Business Process Outsourcing (BPO) in the Philippines - Moral, Isabel; Tajonera, Chris Feli Joy; Madrigal, Dennis (Technium Social Sciences Journal, 2025)
This study examined the levels of occupational stress and coping mechanisms among 132 inbound call center agents of a Business Process Outsourcing (BPO) in the Philippines using a quantitative descriptive-correlational design. The findings revealed that agents experience a moderate level of stress, with workload identified as the primary stressor. Despite this, agents demonstrated a high capacity for coping, primarily using problem-solving strategies. While demographic variables like age, marital status, and tenure did not significantly influence stress levels, sex was found to be a factor in coping, with female agents reporting a greater use of coping strategies. These results suggest a need for tailored, gender-sensitive wellness programs that promote resilience through problem-solving and positive emotional regulation. This research contributes to the academic understanding of stress in the Southeast Asian service industry and offers practical insights for developing evidence-based mental health programs. Keywords: Psychology, Occupational stress, coping mechanism, Call center agents, BPO, Philippines